2019
DOI: 10.1088/1361-6528/aaffac
|View full text |Cite
|
Sign up to set email alerts
|

Intense pulsed light, a promising technique to develop molybdenum sulfide catalysts for hydrogen evolution

Abstract: We have demonstrated a simple and scalable fabrication process for defect-rich MoS2 directly from ammonium tetrathiomolybdate precursor using intense pulse light treatment in milliseconds durations. The formation of MoS2 from the precursor film after intense pulsed light exposure was confirmed with XPS, XRD, electron microscopy and Raman spectroscopy. The resulting material exhibited high activity for the hydrogen evolution reaction (HER) in acidic media, requiring merely 200 mV overpotential to reach a curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…3b, the high-resolution XPS spectrum for Mo 3d of MoS 2 /PCN-223-Fe showed two peaks at 232.65 eV and 229.5 eV corresponding with the binding energy of Mo3d 3/2 and Mo 3d 5/2 , respectively, which suggested that Mo was in +4 oxidation state on PCN-223-Fe surface. [41][42][43] The observed weak peak at 236.2 eV correspond to Mo 6+ 3d 5/2 , which indicated the formation of MoO 3 by oxidation of Mo 4+ . In addition, a very weak peak observed at 227.8 eV corresponding to S 2s.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…3b, the high-resolution XPS spectrum for Mo 3d of MoS 2 /PCN-223-Fe showed two peaks at 232.65 eV and 229.5 eV corresponding with the binding energy of Mo3d 3/2 and Mo 3d 5/2 , respectively, which suggested that Mo was in +4 oxidation state on PCN-223-Fe surface. [41][42][43] The observed weak peak at 236.2 eV correspond to Mo 6+ 3d 5/2 , which indicated the formation of MoO 3 by oxidation of Mo 4+ . In addition, a very weak peak observed at 227.8 eV corresponding to S 2s.…”
Section: Resultsmentioning
confidence: 93%
“…1d, and the spacing of the lattice fringes were 0.62 nm, corresponding to the MoS 2 (002) on PCN-223-Fe. 41 Clearly, MoS 2 nanoparticles were successfully deposited on PCN-223-Fe surface. As control, the as-prepared MoS 2 nanoparticles in the same way aggregated together (Fig.…”
Section: Synthesis Of Pcn-223-fe and Mos 2 /Pcn-223-fe-pcn-223-mentioning
confidence: 99%
“…Intense pulse light (IPL) is a promising postprocess annealing method which can anneal large-area thin films using millisecond duration flashes in a couple of seconds, meeting the rapid fabrication speed for scalable automation of PSCs. [35][36][37][38][39][40][41][42] In this method, the application of large potential to a noble gas-filled lamp, typically xenon, releases an intense flash lasting for milliseconds as a result of the relaxation of excited gas atoms by the high electric potential. [43] The released irradiation carries energetic photons with several hundreds of degrees, which then convert into phonons and instantly anneal the thin-film material.…”
mentioning
confidence: 99%